The Role of Electro-Explosion Alloying with Titanium Diboride and Treatment with Pulsed Electron Beam in the Surface Modification of VT6 Alloy; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Konovalov S. Sergey; Gromov V. Victor; Bataev V. Vladimir; Ivanov Yu. F. Yuriy Fedorovich; Kobzareva T. Tatyana; Semina O. Olga (2015, 2015)
Title screen